The indications and safety of prolonged temporary pacing using active‐fixation leads and externalized pulse generator. Issue 3 (16th February 2021) - Shah, Nisar H; Shah, Parin; Elsayed, Hossam; O'Callaghan, Peter; Leong, Fong T; Yousef, Zaheer
Abstract: Background: Temporary cardiac pacing, conventionally achieved using a passive transvenous pacing wire, can be life‐saving for unstable arrhythmias. However, they run the risk of complications, the longer they remain in‐situ. Externalized prolonged temporary pacing (EPTP), using active‐fixation lead and an externalized pulse generator; may be an alternative for transient pacing indications, concurrent illness or sepsis that precludes permanent pacing. Methods: Sixty‐seven patients (mean age 69 ± 14 years; 82% male) underwent EPTP between November 2011 and April 2019. EPTP was performed in a sterile facility, under fluoroscopy, using active‐fixation leads anchored to the right ventricle septum. Externalized lead was connected to a re‐sterilized pulse generator and secured to anterior chest wall with transparent dressings. EPTP indications and patient outcomes were evaluated. Results: Pacing indications were high‐grade atrio‐ventricular (AV) block (73.2%), sinus arrest (14.9%), overdrive suppression of VT (5.9%) and pause‐dependent VT (4.5%). Reasons for ETPT rather than permanent pacing included: sepsis (38.8%), CIED‐related infection (8.9%), transient pacing indication (25%), to allow further investigations prior to decision on CIED type (22%), and over‐drive arrhythmia suppression (6%). Sixty three percent patients were severely ill in an ICU. Mean duration of pacing was 16 ± 12 days. Sixty seven percent patients subsequently received a CIED and had no evidence of device‐related infection at 1‐year post‐implant. There were three non‐fatal complications during EPTP while no deaths were attributed to EPTP. Conclusion: EPTP is a safe and useful method of prolonged temporary pacing for patients who require chronotropic support, but in whom immediate permanent pacemaker implantation is contraindicated.